Introduction to engineering thermodynamics - Sonntag, Richard E.; Borgnakke, C. (Claus) (New York : John Wiley and Sons, 2001)
This book is about: Untroductory comments; Concepts and definitions; Properties of a pure substance; Law of thermodynamics; ...
Keywords: Engineering; Thermodynamics; Thermodynamics